Role of lipid binding protein, Niemann pick type C-2, in enhancing shrimp sperm physiological function - Thitiporn Khongkha; Alyssa Rattanadechakul; Piyaporn Surinlert; Orawan Thongsum; Supawich Boonkua; Kessiri Kongmanas; Monsicha Somrit; Wattana Weerachatyanukul; Somluk Asuvapongpatana (Heliyon)
Sperm activation occurring in both male and female reproductive tract involves a highly complex series of biomolecular dynamics, particularly on membrane lipids and proteins. In mammals, the universal anticipation in cholesterol (CHO) sequestration plays a role in mammalian sperm maturation/capacitation, subsequently enhancing sperm fertilizing ability. In shrimp, we have previously shown that the level of cholesterol (CHO) is significantly reduced in vas deferens sperm when compared with sperm in the testes, presumably due to the sequestering action of the lipid-binding protein, one of which is Niemann-Pick Type C-2 (NPC2). Here, we used recombinant MrNPC2 protein to treat testicular sperm (Tsp) and quantitatively compared the amount of CHO with non-treated or 2-OH-β-CD treated sperm. HPTLC of the extracted lipids from Macrobrachium rosenbergii sperm revealed the presence of major phospholipids and CHO. Tsp treated with 2-OH-β-CD or MrNPC2 showed lower CHO levels, which was comparable to that of the vas deferens sperm as verified by the Amplex Red assay. Finally, the enhanced levels of protein tyrosine phosphorylation and ionophore-induced AR levels in the MrNPC2 treated Tsp significantly increased in a concentration-dependent manner, similar to that of the Vsp sperm. Altogether, our results indicated the importance of MrNPC2 as CHO moderator in sperm membrane, leading to an enhancement in sperm fertilizing ability.